2022
DOI: 10.1001/jamanetworkopen.2022.34471
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Online Sexual Offenses Against Children in the US

Abstract: ImportanceSexual abuse is increasingly facilitated by technology, but the prevalence and dynamics of such offenses have not been well delineated, making it difficult to design prevention strategies.ObjectiveTo examine the frequency and characteristics of online and technology-facilitated sexual abuse against children and youth.Design, Setting, and ParticipantsIn this nationally representative online survey study performed from November 19 to December 29, 2021, young adults aged 18 to 28 years were asked retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…In a recent study (Finkelhor, Turner, & Colburn, 2022), we found the lifetime prevalence of OCSA in a national sample of young adults was over 16 %. The experiences were varied, occurring across the age spectrum of youth and adolescence, and involving both peer and adult perpetrators who were intimate partners, offline friends, and acquaintances, as well as unknown persons met online (Finkelhor, Turner, & Colburn, 2022).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In a recent study (Finkelhor, Turner, & Colburn, 2022), we found the lifetime prevalence of OCSA in a national sample of young adults was over 16 %. The experiences were varied, occurring across the age spectrum of youth and adolescence, and involving both peer and adult perpetrators who were intimate partners, offline friends, and acquaintances, as well as unknown persons met online (Finkelhor, Turner, & Colburn, 2022).…”
Section: Introductionmentioning
confidence: 89%
“…But, like their offline parallels, these offenses are interrelated (Finkelhor et al, 2021) and they need to be conceptualized and addressed in a more integrated way. In previous work (Finkelhor, Turner, & Coburn, 2022), we helped to advance this goal by developing the definition and operationalization of the more integrated concept of “online child sexual abuse” (OCSA), a more comprehensive concept that incorporates nonconsensual image taking or sharing, forced image recruitment, threatened sharing of sexual pictures, unwanted sexual talk, questions, or sexual act requests by adults, and commercial sexual exploitation, involving sex talk, images, or other sexual activity. In a recent study (Finkelhor, Turner, & Colburn, 2022), we found the lifetime prevalence of OCSA in a national sample of young adults was over 16 %.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arguments have been made that requiring parental consent for adolescents aged 16 years or older is an expression of overprotection 2,21–23 and may not be legally justified in social science research 2 . Perhaps, the same claim can be made for adolescents as young as 12 years given that adolescents have been shown to have a greater capacity and maturity to understand the significance of research and the implications of the risk and benefits to themselves than expected 2,17,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Like other social activities, criminal offenses have been migrating to the digital environment. Recent research shows that over 15% of children and youth report technology-facilitated offenses, including unwanted sexual solicitation, non-consensual image sharing and taking, or sextortion (Finkelhor et al, 2022). Concerns have been raised about the harmful features of these digital offenses, including that technology has facilitated more ready access to children by predatory strangers and adults, that it has reduced inhibitions to aggression, and that is has heightened the impact by rendering the aggressions more socially visible, pervasive, and harder to escape from (Underwood & Ehrenreich, 2017).…”
Section: Introductionmentioning
confidence: 99%